NOTES FROM THE EDITOR’S DESK - VOL. 09, NO. 2, 2020 - Azharsyah Ibrahim (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2020)
Alhamdulillah, thanks to Allah, that Volume 9 Number 2 (July - December edition) 2020 has been published on time. As always, in the attempts to maintain the quality, each article that has passed the initial review will have gone through a rigorous review process. In this issue, we publish seven articles out of dozens that have been submitted into our online system. The accepted articles discuss various topics within the field of Islamic economics and finance. Finally, I would like to thank those who have been helpful in organizing the day-by-day operation of the journal, including our editors, reviewers, and administrative staff. We also thank our friends at the Rumah Jurnal UIN Ar-Raniry, who has also been supportive in keeping the journal meet the academic standards.